2021
DOI: 10.1097/fjc.0000000000001099
|View full text |Cite
|
Sign up to set email alerts
|

Sodium–glucose cotransporter-2 Inhibitors in Heart Failure: An Updated Systematic Review and Meta-analysis of 13 Randomized Clinical Trials Including 14,618 Patients With Heart Failure

Abstract: Sodium-glucose cotransporter-2 (SGLT-2) inhibitors showed benefit in patients with heart failure. In this updated metaanalysis, we evaluate the therapeutic efficacy and safety of SGLT-2 inhibitors in patients with heart failure. Different electronic databases were searched to find relevant articles. RevMan 5.4 was used for pooling data using a random/fixed-effects model, complemented by several sensitivity and subgroup analyses. A total of 13 randomized clinical trials including 14,618 patients with heart fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…In previous meta-analysis, adverse events were similar between SGLT2 inhibitors and placebo, except for a mild increase in genital infection in the SGLT2 subgroup. This is concordant with the reassuring safety information regarding SGLT2 inhibitors' use during the hospitalization [75][76][77]. Taking all this data into account, we could hypothesize that the relative benefit of SGLT2 inhibitors on HF outcomes remains constant regardless of target population.…”
Section: Practical Management: When To Start Sglt2 Inhibitors During ...supporting
confidence: 78%
“…In previous meta-analysis, adverse events were similar between SGLT2 inhibitors and placebo, except for a mild increase in genital infection in the SGLT2 subgroup. This is concordant with the reassuring safety information regarding SGLT2 inhibitors' use during the hospitalization [75][76][77]. Taking all this data into account, we could hypothesize that the relative benefit of SGLT2 inhibitors on HF outcomes remains constant regardless of target population.…”
Section: Practical Management: When To Start Sglt2 Inhibitors During ...supporting
confidence: 78%
“…Marfella et al, The accumulated evidence from these studies highlights the therapeutic potential of SGLT2 inhibitors, particularly Empagliflozin, in the management of AHF. It is worth noting that the beneficial effects of these drugs appear to extend beyond their initial purpose as glucose-lowering agents in T2DM [20][21][22]. These studies suggest an additional cardioprotective effect, translating into improved patient outcomes, a notion supported by the current literature [23][24][25][26].…”
Section: Discussionmentioning
confidence: 70%
“…Subgroup analysis showed no significant associations between SGLT2i and SBP in terms of baseline characteristics, baseline anti-HF drugs administered, or type of study. A meta-analysis indicated that SGLT2i improved cardiovascular outcomes and that the clinical benefit was comparable between diabetic and nondiabetic individuals, men and women, and younger and older patients with underlying HF [ 55 ]. Further research is needed to identify the most suitable populations for SGLT2i.…”
Section: Discussionmentioning
confidence: 99%